Peripheral blood progenitor cell transplantation in multiple myeloma following high-dose melphalan-based therapy - Goldschmidt, Hartmut; Hegenbart, Ute; Wallmeier, M.; Hohaus, Stefan; Engenhart, Rita; Wannenmacher, Michael; Haas, Rainer (Advances in hematopoietic stem cell transplantation and molecular therapy, 1998)
The objective of our study was to evaluate the efficacy and toxicity of a high-dose melphalan-based therapy with or without total body irradiation (TBI) followed by peripheral blood progenitor cell (PBPC) transplantation in patients with multiple myeloma. Between June 1992 and June 1996, 104 patients (71 male, 33 female) with a median age of 51 years (range 30-65 years) underwent transplantation at our center. PBPC were mobilized using high-dose chemotherapy followed by treatment with G-CSF. Fifty patients were treated with TBI+melphalan 140 mg/m2 while 54 patients received melphalan 200 mg/m2. Following PBPC autografting, the median time to attainment of platelets ≥20×109/l and neutrophils ≥0.5×109/l was 11 and 14 days, with no difference between the treatment groups. In the TBI group significantly longer periods of total parenteral nutrition were required due to the occurrence of severe mucositis. Two patients from the TBI group died of transplantation-related complications. Following high-dose treatment, remission state improved in 43 out of 102 patients. No statistically significant advantage in reaching complete or partial remission was observed with TBI+high-dose melphalan compared to the treatment with high-dose melphalan alone. The optimal high-dose treatment, with particular reference to the inclusion or omission of TBI, should be prospectively investigated.
Gesehen am 28.04.2025